Detection of X‐Ray Doses with Color‐Changing Hackmanites: Mechanism and Application (Advanced Optical Materials 20/2021). Issue 20 (18th October 2021) - Vuori, Sami; Colinet, Pauline; Norrbo, Isabella; Steininger, Ralph; Saarinen, Timo; Palonen, Heikki; Paturi, Petriina; Rodrigues, Lucas C. V.; Göttlicher, Jörg; Le Bahers, Tangui; Lastusaari, Mika
Abstract : Hackmanites are a family of optically intelligent materials having the ability for reversible photochromism upon X‐ray exposure. In article number 2100762, Mika Lastusaari, Tangui Le Bahers and co‐workers elucidate how X‐rays induce the pairing of electrons and holes to form eraseable color centers in these materials. Understanding their coloration mechanism opens up new possibilities as highly attractive alternatives in future X‐ray dosimetric and photochromic imaging applications.